2014
DOI: 10.1002/jsfa.6671
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and anti‐fatigue activities of egg white peptides prepared by pepsin digestion

Abstract: Among the four peptide fractions, EWPs2 possessed the strongest antioxidant activity and exhibited an anti-fatigue effect. The experimental data could clarify partially the anti-fatigue mechanisms of EWPs and provide an important basis for developing EWPs as safe and natural antioxidants and anti-fatigue agents for wide use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 25 publications
1
31
0
Order By: Relevance
“…In addition, they have a metal chelation potential (Ding et al 2015). The presence of Tyr and Phe amino acids in the peptides is related to scavenging free radical properties (Sun et al 2014). In addition, the His residues are directly associated with metal chelating property (Gallegos-Tintore The exact mechanism by which HgCl 2 can penetrate through the BBB is unclear.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…In addition, they have a metal chelation potential (Ding et al 2015). The presence of Tyr and Phe amino acids in the peptides is related to scavenging free radical properties (Sun et al 2014). In addition, the His residues are directly associated with metal chelating property (Gallegos-Tintore The exact mechanism by which HgCl 2 can penetrate through the BBB is unclear.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…These findings may explain the observed significant differences in serum creatinine kinase levels among the three groups. The antifatigue effect has also been reported for pepsin digests from EWP, and the absorption rate was considered a likely contributing factor (Sun et al., 2014). Therefore, this difference in absorption rates may be involved in the various increases in swimming time.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, antioxidant and antifatigue effects were observed with pepsin‐degraded products of EWP at a low dose of 0.2 mg/g/day (Sun et al., 2014). As pepsin is a typical enzyme found in the stomach, it is reasonable to expect effects similar with those of the ingestion of unprocessed EWP, although it may be less effective.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations